2014
DOI: 10.1074/jbc.m113.494575
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pregnane X Receptor in Obesity and Glucose Homeostasis in Male Mice

Abstract: Background: PXR is a xenobiotic nuclear receptor that defends against toxic agents. Results: In male mice fed a HFD, the mouse PXR gene promoted obesity, whereas mice lacking the PXR or possessing the human transgene were hyperglycemic. Conclusion: The impact of PXR on HFD-induced obesity and hyperglycemia is species-dependent. Significance: The current data provide in vivo significance of PXR in metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 73 publications
8
97
3
Order By: Relevance
“…The dichotomy of resistance to DIO and altered glucose homeostasis that we noted is not unprecedented (9,50) and would suggest that in IL-15R␣ Ϫ/Ϫ mice, the increased utilization of fatty acids competes with utilization of glucose as a substrate (12,26,42). Similarly, muscle-specific PGC-1␣ overexpression also induces a muscle oxidative phenotype with constitutively higher fat oxidation at the expense of glucose tolerance (9).…”
Section: Discussionmentioning
confidence: 73%
“…The dichotomy of resistance to DIO and altered glucose homeostasis that we noted is not unprecedented (9,50) and would suggest that in IL-15R␣ Ϫ/Ϫ mice, the increased utilization of fatty acids competes with utilization of glucose as a substrate (12,26,42). Similarly, muscle-specific PGC-1␣ overexpression also induces a muscle oxidative phenotype with constitutively higher fat oxidation at the expense of glucose tolerance (9).…”
Section: Discussionmentioning
confidence: 73%
“…Total RNA was isolated from frozen liver tissues using the Trizol reagent according to the manufacturer's protocol (Invitrogen, Carlsbard, CA). Total RNA (5 mg) was reverse transcribed into cDNA with random hexamer primers using a Tetro cDNA Synthesis Kit (Bioline, Taunton, MA) as we previously described (Spruiell et al, 2014b). The cDNA was then diluted 20-fold with water and subjected to real-time quantitative polymerase chain reaction (PCR) by the SensiFast SYBR Hi-ROX Kit (Bioline) to quantify the mRNA levels of peroxisome proliferator-activated receptor a (PPARa), PPARg, sterol regulatory element-binding protein-1c (SREBP-1c), CPT1 (carnitine palmitoyltransferase 1), ACOX-1 (acylCoA Oxidase 1), L-FABP-1 (liver-type fatty acid-binding protein 1), microsomal triglyceride transfer protein (MTTP), fatty acid translocase (CD36), ACC-1a (acetyl-CoA carboxylase 1a), FAS (fatty acid synthase), SCD1 (stearoyl-CoA desaturase-1), and phosphatidylethanolamine N-methyltransferase (PEMT).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, PXR plays an important role in the xenobiotic metabolism and excretion. In addition to this well-known function, recent studies have expanded the roles of PXR, which include the regulation of glucose or lipid metabolisms in the liver (Sui et al, 2011;Chang and Waxman, 2006;Hukkanen, 2012;Gotoh and Negishi, 2015;Spruiell et al, 2014). In addition, we have recently demonstrated that PXR activation enhances hepatocyte proliferation mediated by CAR or peroxisome proliferator-activated receptor α (PPARα) activation: Although treatment of mice with pregnenolone 16α-carbonitrile (PCN), a PXR agonist, alone did not induce hepatocyte proliferation, co-treatment of mice with PCN and CAR or PPARα agonist showed intense hepatocyte proliferation compared to single treatment with CAR or PPARα agonist (Shizu et al, 2013), which probably results from the PXR-mediated down-regulation of cell cycle suppressor genes (Shizu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%